Sex-Specific Effects of Vitamin D Status on the Metabolic Profile in Prediabetic Subjects - Teresa Gisinger; Michael Leutner; Evelyne Wohlschläger-Krenn; Robert Winker; Sonja Nistler; Georg Endler; Alexandra Kautzky-Willer (International Journal of Endocrinology)
Introduction. We aim to investigate the effect of vitamin D on metabolic parameters in a population with prediabetes and to detect possible sex differences. Methods. In 621 patients with diagnosed prediabetes, glucose, lipid, and anthropometric parameters were measured. Furthermore, the interaction of 25-OH-vitamin D (25-hydroxyvitamin D) with metabolic and glucose metabolism parameters was analysed in the total prediabetic population, as well as after stratification by sex (female vs. male prediabetic subgroup), by logistic regression. Results. 25-OH-vitamin D was negatively related to cholesterol, BMI, fatty liver index, insulin, and HOMA-IR. Especially in the male prediabetic cohort, 25-OH-vitamin D levels negatively correlated with total cholesterol levels (r = −0.17, p=0.001), with triglycerides (r = −0.17, p=0.001), and with HbA1c levels (r = −0.14, p=0.010). Only in the female cohort with prediabetes, we found a negative correlation of 25-OH-vitamin D levels with systolic (r = −0.18, p=0.005) and diastolic blood pressures (r = −0.23, p<0.001). Conclusion. In this study, in females with prediabetes, 25-OH-vitamin D was notably related to a more favourable metabolic profile, including lower total cholesterol and higher HDL cholesterol levels. On the contrary, in men with prediabetes, there was a stronger association between 25-OH-vitamin D and cholesterol-HDL quotient, as well as fatty liver index was observed in the male prediabetic subgroup. Therefore, sex differences should be considered in future studies on vitamin D and glucose tolerance status.